INOVASI PRODUK KEUANGAN SYARIAH UNTUK GENERASI Z - Supriana, Evany Melia; Herawati, Endang; Aprilisa, Meri; Aulia, Lia Fita; Febriyansyah, Diah Irwan (Jurnal Ekonomi & Bisnis, 2024)
The rapidly evolving world of sharia finance faces unique challenges and opportunities in integrating Sharia principles with modern financial innovation. This article explores current trends and future potential in product innovation in sharia finance, with a focus on technology integration, shariah compliance, and social responsibility. The purpose of crafting this article is to bolster Islamic financial literacy and cultivate interest among Generation Z in engaging with sharia-compliant banking products. Additionally, it aims to fortify the role of sharia financial institutions in propelling the technology sector in Indonesia. This study uses a qualitative method with a literature research approach to find out more deeply about the application of innovative ideas for sharia financial products for generation Z. The findings of the research provide an overview of how Generation Z responds to technological developments by considering accessibility in accessing sharia financial products, thereby enabling Generation Z to access financial services anytime and anywhere. Furthermore, the technological innovations implemented have the potential to augment the financial literacy and interest of Generation Z in availing themselves of sharia-compliant financial services.